2002
DOI: 10.1590/s0011-52582002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Incentivos Eleitorais, Partidos e Política Orçamentária

Abstract: O uso de variáveis institucionais na análise comparada seguiu um curso próprio. Com o tempo, no entanto, o paradigma dominante nos estudos legislativos norte-americanos foi incorporado à literatura comparada. Adotou-se, de forma generalizada, a premissa segundo a qual políticos querem, antes de tudo, se reeleger e, para tanto, buscam estabelecer vínculos pessoais com seus eleitores. Mais do que isso, passou-se a dar por estabelecido que as conseqüências daí derivadas pela interpretação distributivista da polít… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
20

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 7 publications
(3 reference statements)
0
9
0
20
Order By: Relevance
“…The Brazilian legislature has limited opportunities to influence the federal budget. The Constitution gives the executive the exclusive authority to initiate the budget proposal and the credit laws (leis de crédito), which modify the budget throughout the year in response to changes in tax collection and economic circumstances (Figueiredo and Limongi 2002). once the annual budget proposal (Proposta de Lei Orçamentária) has been drafted by the executive, setting the expected total revenues and estimated expenses for the following year, it is sent to the legislature for review and debate.…”
Section: The Budget In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brazilian legislature has limited opportunities to influence the federal budget. The Constitution gives the executive the exclusive authority to initiate the budget proposal and the credit laws (leis de crédito), which modify the budget throughout the year in response to changes in tax collection and economic circumstances (Figueiredo and Limongi 2002). once the annual budget proposal (Proposta de Lei Orçamentária) has been drafted by the executive, setting the expected total revenues and estimated expenses for the following year, it is sent to the legislature for review and debate.…”
Section: The Budget In Brazilmentioning
confidence: 99%
“…According to Amorim Neto and Tafner (2003), the large number of provisional decrees passed by the president and approved by the legislature is the byproduct of a strong coalition government-that is, the large number of decrees represents a deliberate delegation of power from legislature to president. Figueiredo and Limongi (2002) have also established that presidents with weak legislative support, such as Fernando Collor de Mello in the early 1990s, use decrees less frequently. The composition of the cabinet and the proportionality between the cabinet and the government coalition within administrations are additional factors to consider in the case of Brazil (Amorim Neto, Cox, and McCubbins 2003).…”
Section: Case Selectionmentioning
confidence: 99%
“…The presidency is not divisible in presidential elections, and this fact encourages one-party executives. This is not to say that some form of government approaching a "coalition government" is not possible-as the Argentine, Brazilian, and Uruguayan examples illustrate, a president may choose to bring ministers from other parties into the government to strengthen congressional alliances (Altman 2000;Ames 2001;Amorim Neto and Tafner 2002;Figueiredo and Limongi 2002). Yet the withdrawal of one or more parties from the government does not threaten the position of the President like parliamentary systems where the collapse of the government imperils the position of the prime minister.…”
Section: Sources Of Fragmentation Within the Cabinetmentioning
confidence: 99%
“…The district magnitude varies from 8 to 70 representatives by state. Despite being a multi-party system, an important literature has shown that the internal decision-making process of the Brazilian Congress is characterized by centralized organization and political party coordination (Figueiredo and Limongi, 2002).…”
Section: How the Brazilian Budget Process Workmentioning
confidence: 99%